Modelo PAMPA para estudo comparativo da permeabilidade de compostos fenólicos isolados e a partir de extratos de plantas medicinais - Bianchetti, Paula (2018)
The use of natural compounds from the Brazilian national flora provides the population access to treatment of various disorders and the development of new therapeutic products. Therefore, it is important that permeation tests of these compounds are performed in order to have complete therapeutic efficacy. To this end, permeation models are used. Some of these models are called PAMPA (Parallel Artificial Membrane Permeability Assays) and mimic different types of cell membranes and the permeability of these tissues, such as the gastrointestinal tract, transepidermal route, and blood/brain pathway. The objective of this study is to evaluate the permeation of phenolic compounds in different permeation models (cutaneous, gastrointestinal and blood-brain barrier) using modified membranes of PAMPA type. For this purpose, polyvinyl difluoride (PVDF) membranes were modified in three absorption models: gastrointestinal, cutaneous and hematoencephalic. The antioxidants present in these plants were already evaluated through mass spectrometry (LC-MS / MS) and from this study eight antioxidants were evaluated, which presented the highest amount available. The evaluations of the permeated components were performed using High- Performance Liquid Chromatography with Diode Arrangement Detector (HPLC-DAD) and amperometric (HPLC-PAD). For an adequate use of the membranes, they were characterized with surface evaluation by scanning electron microscopy and ion diffusion test. It was possible to verify that the modified membranes – PAMPAPELE, PAMPATGI e PAMPABHE – present a good model for mimicking cutaneous permeation, gastrointestinal tract, and blood-brain barrier. It was observed from the studies carried out that the chlorogenic acid has a better permeation profile in the three membranes, both in the individual active and in the mixture. In the evaluation of the effective coefficient permeation of crude extracts at 10%, in the membrane PAMPAPELE and PAMPATGI very similar permeation values were observed in both membranes, with permeation prominence for chlorogenic acid. In addition, in the evaluation of the mixed compounds and in the extracts, it was possible to infer the synergistic action. It is observed in the extracts that according to the chemical composition of each plant, there is a favoring of the passage and consequent minimization of action of others. In the permeation of the mixture, the intermolecular interaction are evident, when compared to the individual permeation of the compounds and to the extracts themselves.